On the flow of a viscous thin layer on an inclined plane driven by a constant surface tension gradient - Emilia Borşa; Călin Ioan Gheorghiu (Journal of Numerical Analysis and Approximation Theory, 2001)
Steady flow of a thin layer (trickle, rivulet) of viscous fluid down an inclined surface is considered, via a thin-film approximation. The work extends the study by Duffy and Moffatt [7] of gravity-driven thin trickle of viscous fluid to include the effects of a surface tension gradient. It acts on the free surface of the layer. At the same time the work tries an alternative analysis to our tradi- tional approaches exposed in [6] and the papers quoted there. Asymptotic and numerical results for several values of volume flux and surface tension gradients are carried out.